2016
DOI: 10.1016/j.jmii.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of late-onset neonatal sepsis in Taiwan: A matched case-control study

Abstract: Parenteral nutrition was a significant and independent risk of late-onset neonatal sepsis. This risk should be considered when implementing early parenteral nutrition in NICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 20 publications
8
24
0
1
Order By: Relevance
“…CoNS was the most commonly isolated pathogen during the 1992e2001 and 2008e2013 periods in our NICU, similar to other reports from Taiwan. 3,4,12 Because of the high proportion of CoNS infection, Gram-positive organisms were the dominant pathogens in our NICU. CoNS BSI may be related to prolonged central line catheter use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CoNS was the most commonly isolated pathogen during the 1992e2001 and 2008e2013 periods in our NICU, similar to other reports from Taiwan. 3,4,12 Because of the high proportion of CoNS infection, Gram-positive organisms were the dominant pathogens in our NICU. CoNS BSI may be related to prolonged central line catheter use.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm and VLBW infants often require aggressive interventions, such as mechanical ventilator, intravascular catheterization, parenteral nutrition supplement, and prolonged length of hospitalization. 11,12 Late-onset infection is associated with all these managements. Although the ratio of these more vulnerable patients remained high, better outcome was found through the years.…”
Section: Discussionmentioning
confidence: 99%
“…16 A retrospective, matched, caseecontrol study performed on 164 Taiwanese case infants with bloodstream infections and as many controls showed that parenteral nutrition (OR 6.07; 95% CI, 1.14e32.32; p Z 0.034) and intraventricular hemorrhage (OR, 2.68; 95% CI, 1.20e5.99; p Z 0.017) were independently associated with bloodstream infections after multivariate analysis. 17 Moreover, a retrospective United States (US) cohort study, evaluating NICUs patients with peripherally inserted central catheters from 2003 to 2010, showed that catheter removal due to adverse events is significantly associated with LOS and that antibiotic use before removal is not associated with a decline in sepsis rate. 18…”
Section: Losmentioning
confidence: 99%
“…Kung et al [35] affirm that infants in NICU have a higher incidence of Candida infections than any other pediatric or adult population. The predisposing factors were evaluated in Taiwan using a retrospective matched case-control study conducted in the NICUs of a teaching hospital from July 2003 to June 2006.…”
Section: Neonatal Candida Infectionsmentioning
confidence: 99%